Metal dispersion and catalytic activity of trimetallic Pt-Re-Sn/Al 2O3 naphtha reforming catalysts - Pieck, Carlos Luis (2005)
The chemisorption of CO over mono-, bi- and trimetallic naphtha reforming catalysts containing Pt, Re and Sn in the metallic function was studied. The temperature-programmed reduction (TPR) results show that there are important interactions among the metals. The CO chemisorption experiments were performed in a pulse equipment. Pulses of the adsorbate (CO) were successively injected to the system until saturation and the exposed Pt was determined from the amount of adsorbate irreversibly adsorbed. The exposed or accessible Pt obtained was compared with that one determined by the classical static method and it was also correlated with the results of catalytic activity of the metal function (cyclohexane dehydrogenation at 400 °C, 0.1 MPa, H2/CH = 30). The CO chemisorption results indicate that it is possible to determine in an easy way the metallic dispersion of Pt/Al2O3 monometallic catalysts and that the same method can be applied to measure the exposed Pt on bimetallic Pt-Re and Pt-Sn catalysts and trimetallic Pt-Re-Sn catalysts. The values obtained from CO adsorption have very good repeatability and are proportional to the dehydrogenating activity of the catalyst. The latter correlation has a few outliners which were attributed to the electronic effects exerted by Sn and Re over Pt that modify differently the metal activity and the capacity to chemisorb CO.